A Short Comparative Study of Corporate Governance in European National Legal Systems - Dumitru, Ovidiu Ioan; Vavura, Nicolae Marius (Technium Social Sciences Journal, 2020)
Corporate Governance has developed immensely in the last decades mainly due to the negative effects on shareholders’s of management decisions leading to a continuous conflict to be solved by the policymakers and academics. After the publication of the Cadbury Report, we noticed an increase interest in drafting corporate governance codes, the American and European legislators being the most active, but recent financial crisis reduced confidence in the results of corporate governance quality, some authors asserting even that the poor implementation of the policies in the area have leaded to the crisis. This paper wants to show the diversity of corporate governance standards present today in different national legal systems, by comparing its main elements like protection of shareholders and stakeholders’ interests, board structures and operations and control, oversight and reporting.